(untitled) (Colombia Medica, 2013)
It is an autosomal dominant vascular disorder, which has a variety of clinical manifestations, with epistaxis being one of the most common. Many treatment options exist for epistaxis, but with no consensus on which is the method of choice. We describe the case of a patient with hereditary hemorrhagic telangiectasia (HHT) secondary epistaxis with septoplasty managed with synthetic hard graft, which improved intensity and frequency of bleeding episodes. This technique is a variant of the septodermoplasty described by several authors, but the use of synthetic dura can help in obtaining better results and avoid taking skin grafts from other sites different from the surgical site.